Cultural Beliefs and Family Well-being: A Narrative Review - Seyed Alitabar, Seyed Hadi (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: This review aims to explore the influence of cultural beliefs on family well-being, highlighting how these beliefs impact family dynamics, health behaviors, and support systems across diverse cultures.Methods and Materials: Utilizing a descriptive narrative review approach, this study systematically searches through databases like PubMed, PsycINFO, Scopus, and Web of Science, focusing on literature from 2000 to 2023. The review integrates studies examining the impact of cultural beliefs on various aspects of family well-being, including mental health, relationships, and parenting practices.Findings: The synthesis reveals that cultural beliefs deeply influence family well-being, affecting areas such as family dynamics, mental health, parenting practices, and family resilience. The review highlights both the supportive and detrimental effects of these beliefs, demonstrating their critical role in shaping health behaviors and intervention outcomes.Conclusion: Recognizing and integrating cultural beliefs into healthcare and social support systems is essential for improving family well-being. Future research should aim at longitudinal and culturally specific studies to better understand these complex influences.